Gallstone Ileus: Unfortunate Encounter - Ya’acob, Mohammad Zawawi; Mohamad, Ikhwan Sani; Meng, Leow Voon; Yahya, Maya Mazuwin; Vellasamy, Nagarajan T (Bangladesh Journal of Medical Science, 2024)
Gallstone disease is a common burden that affect worldwide that carry broad spectrum of its complications and severities. Gallstone ileus (GSI) remained the rare complication that arise form gallstone disease that mainly affected the elderly population. The mainstay of treatment for GSI is to relieve the small bowel obstruction by extraction of the impacted gallstone. Surgical options for GSI remained the long-standing arguments involve single-staged procedure (enterolithotomy, cholecystectomy and fistula repair) or twostaged procedure (enterolithotomy alone, and cholecystectomy with fistula repair later). We reported a case of a 76-year-old male who presented with symptoms of small bowel obstruction and computed tomography (CT) of abdomen confirmed the presence of calcified lesion at ileum with pneumobilia which was successfully managed with two-staged procedure. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 272-275